Synthesis and in vitro Amebicidal Activity of Some N.N´ -Disubstituted Diamine Dihydro- Chlorides and N-Substituted Benzenepropenamides - Kachroo, P.L.; Gupta, Rajive; K. Gupta, Avinash (Asian Journal of Chemistry, 2010)
Synthesis of some N,N´-di-[3-(2,4-dialkoxy-5-alkylphenyl)propyl]-1,3-propanediamines and N-substituted 2,4-dialkoxy-5-alkylbenzenepropenamides have been described. The compounds have been tested in vitro for amebicidal activity against axenically grown E. histolytica.